Antibacterial, antioxidant, and anticancer activities of Penicillium citrinum Thom. endophytic in Jatropha heynei - Gowdru Basanna Ashoka, Manchanahally Byrappa Shivanna (Journal of Applied Pharmaceutical Science, 2023)
In the present study, the leaf, fruit, and root samples of Jatropha heynei were incubated using potato dextrose agar, malt extract agar, czapek dox agar, and water agar methods to determine colonization frequency and diversity indices of endophytic fungi. Thirty three endophytic fungal species of 20 genera were recovered from 5,400 segments of J. heynei and were identified based on their morphological characteristics. Species richness was high in leaf followed by root and fruit. Diversity indices varied depending on the season and different plant parts. The metabolites of endophytic fungus Penicillium citrinum were tested for antibacterial, antioxidant, and cytotoxic studies in vitro. The culture filtrate (CF) extract of P. citrinum showed high antibacterial activity to Pseudomonas syringae (zone of inhibition 17.65 ± 1 mm) and Staphylococcus aureus (zone of inhibition 16.32 ± 0.5 mm). The antioxidant potential was determined by cyclic voltammetry method based on the detection of redox potential of metabolites. The CF extract exhibited significant cytotoxic effect in both A549 and MCF-7 cell lines at 500 μg ml−1 with IC50 values of 280.7 and 283.0 μg ml−1, respectively. Orbitrap high resolution liquid chromatography mass spectroscopy (OHR-LCMS) analysis of CF extract documented 21 bio-active compounds; major compounds include 8-hydroxyquinoline, trigonelline, spectinomycin, psoralidin, nicotinic acid, kanosamine, sulfamethazine, artemisinin, and other compounds with bioactive properties. Fourier Transform Infrared Spectroscopic analysis confirmed the presence of functional groups that are attributed to antibacterial, antioxidant, and anticancer compounds profiled in the OHR-LCMS.
Keywords: Jatropha heynei, OHR-LCMS, A549 and MCF-7 cancer cell lines, cyclic voltammetry, FTIR